2022
DOI: 10.1186/s12906-022-03794-9
|View full text |Cite
|
Sign up to set email alerts
|

Water extract from artichoke ameliorates high-fat diet-induced non-alcoholic fatty liver disease in rats

Abstract: Background The “multiple-hit” hypothesis is currently the most widely accepted theory for non-alcoholic fatty liver disease (NAFLD) pathogenesis. The present study aimed to investigate the effects of the water extract of artichoke (WEA) on NAFLD and its underlying mechanism. Methods Rats were fed a high-fat diet (HFD) for 8 weeks to induce NAFLD and then treated with WEA at three doses (0.4, 0.8, and 1.6 g/kg body weight, BW) for 8 weeks. At the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Studies have shown that artichokes contain high levels of chlorogenic acid, cynarin, flavonoids, and other active compounds [26,27].Among these, chlorogenic acid has been reported to improve glucose homeostasis by increasing glucose tolerance and insulin sensitivity [28] and improve high-fat diet-induced hepatic steatosis and IR in mice fed a high-fat diet [29], and flavonoid supplements improve IR in overweight and obese participants [30]. Our previous study has consistently demonstrated that artichoke water extract may attenuate IR by activating PI3K/Akt signaling in the liver of rats with nonalcoholic fatty liver disease [22]. In this study, our results revealed that AWE has an inhibitory effect on PA-induced IR in HepG2 cells by regulating glucose metabolism involved in IRS1/PI3K/Akt pathway by reducing gluconeogenesis and increasing glycogenesis, which may be due to inhibition of PA-induced ER stress.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies have shown that artichokes contain high levels of chlorogenic acid, cynarin, flavonoids, and other active compounds [26,27].Among these, chlorogenic acid has been reported to improve glucose homeostasis by increasing glucose tolerance and insulin sensitivity [28] and improve high-fat diet-induced hepatic steatosis and IR in mice fed a high-fat diet [29], and flavonoid supplements improve IR in overweight and obese participants [30]. Our previous study has consistently demonstrated that artichoke water extract may attenuate IR by activating PI3K/Akt signaling in the liver of rats with nonalcoholic fatty liver disease [22]. In this study, our results revealed that AWE has an inhibitory effect on PA-induced IR in HepG2 cells by regulating glucose metabolism involved in IRS1/PI3K/Akt pathway by reducing gluconeogenesis and increasing glycogenesis, which may be due to inhibition of PA-induced ER stress.…”
Section: Discussionmentioning
confidence: 97%
“…The harvested plants were identified in the botany laboratory of hunan college of arts and sciences, changed, by Professor Youlin Peng and a voucher specimen [CXJ24] was deposited at the herbarium of the laboratory of the center for biological and agricultural resources of Hunan College of Arts and Sciences. AWE (containing 1.2% chlorogenic acid, 4.8% cynarin) was supplied by Huimei Agricultural Science and Technology Co. Ltd. (Hunan, China) as described in our previous study [22]. Sterile bovine serum albumin (BSA) coupled sodium salt of PA solution (2.5% BSA) and control solvent (containing 2.5% fatty acid-free BSA) was ordered from Shanghai Siduorui Biotechnology Service Co., Ltd (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeoylquinic acids, for example, have been shown to disrupt bacterial cell walls [ 44 ], while flavonoids have been shown to interfere with microbial enzyme activity [ 45 ]. These compounds collectively demonstrate a broad spectrum of antimicrobial activity against bacteria, fungi, and even some viruses [ 46 ]. The specific molecular targets of artichoke extracts vary, providing a versatile profile for combating diverse pathogens.…”
Section: Antimicrobial Activity Of Artichokementioning
confidence: 99%
“…Artichoke leaf, head, and stem extracts have shown inhibitory effects on the growth of common pathogens such as Staphylococcus aureus , Escherichia coli , and Salmonella spp. [ 46 ].…”
Section: Antimicrobial Activity Of Artichokementioning
confidence: 99%